MEREVITALISASI MAQÂSID AL-SYARÎ ‘AH SEBAGAI PARADIGMA IJTIHAD DALAM LEGISLASI HUKUM ABSTRAK ISLAM DI INDONESIA - Ahmad Ali MD (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2015)
This paper argues that Maqâsid al-Syarî‘ah should be revitalized as a paradigm of ijtihâd in the legislation of Islamic law in Indonesia in order to preserve and protect al-Kullîyah al-Khamsah (Five Universal Principles).In this way, the norms of Islamic law becomes more meaningful instead of normative, and it becomes a legally binding law without losing its substance. The substance of Islamic law is the soul of mercy for the worlds (rahmatan li al-‘âlamîn), namely a sense of justice, goodness and truth. The revitalization of Maqâsid al-Syarî‘ah is conducted through the mechanism of al-Siyâsah al-Syar‘îyah (legitimate policy). This mechanism is manifested by the issue of fatwa by authorized religious institutions, such as the Majelis Ulama Indonesia (Indonesian Ulama Council), Bahts al-Masâ’il Nahdhatul Ulama (LBM NU), and Majelis Tarjih Muhammadiyah. After that, the results of this arad are absorbed or adapted to the legislation. The formulation of the arad should also pay attention to the five authoritative devices of Khaled Abou El-Fadl’s version, namely honesty, seriousness, comprehensiveness, rationality and self-restraint. Such process and mechanism are the essensials of comprehensive ijtihâd (collective ijtihâd, creative-inovative and implementable).